HUBUNGAN MOTIVASI DAN PELATIHAN TERHADAP PRESTASI KERJA ANGGOTA KONTRAK SAT POL PP KOTA LUBUKLINGGAU - Irma Idayati; Wawan Fransisco; Hengki Firmanuddin (Jurnal Media Ekonomi (JURMEK), 2018)
This study aims to determine the relationship of education and training to the work performance of members of the Lubuklinggau City Police Sat contract. The time of the study was carried out for 9 months from November 2017 to August 2018. The population in this study were 54 members of the Lubuklinggau City PP Sat Contract. Sampling was done by means of saturated sampling. The study sample was 54 people. Data collection techniques in writing this study using observation, documentation and questionnaire. The analysis technique uses simple regression analysis, correlation test, determination test, t test and F test. Based on the results of data analysis and discussion that has been described in the previous chapter, it can be concluded that: 1) There is an educational relationship to the work performance of Sat Pol contract members PP Lubuklinggau City. This is based on the results of the t-test calculation obtained by the data of Education variable (X1) on Work Achievement (Y) shows that the value of tcount = 2.081 is greater than the value of t table (1.675) with a significance level of sig. = 0.005. 2) There is a training relationship to the work performance of members of the Lubuklinggau City PP Sat Contract. This is based on the results of t-test calculations known that the Training Variable (X2) on Job Performance (Y) shows the value of tcount = 5.770 greater than the value of t table (1.675) with a significance level of sig. = 0.005. 3) There is a relationship between education and training on the work performance of members of the Lubuklinggau City PP Sat Contract. This is based on the recapitulation of the results of multiple linear regression tests, obtained that the calculated F value is 72.825> Ftable = 3.18 and the level of significance simultaneously sig F is 0,000.